Trade unions and the real Living Wage: survey evidence from the UK. Issue 4 (21st September 2018) - Heery, Edmund; Hann, Deborah; Nash, David
Abstract: This article uses evidence from a survey of accredited Living Wage Employers to examine the extent to which trade unions have supported, campaigned for and been involved in the introduction of the voluntary or 'real' Living Wage in the UK. It reports that while unions tended to view the adoption of the Living Wage favourably and to support its introduction they typically were not heavily involved either in the initial decision to adopt the standard or in its implementation. This pattern of findings, it is suggested, is consistent with the union response to corporate social responsibility initiatives and provides only limited support for the commonly argued position that 'economic justice' movements provide fertile ground for the development of union‐community coalitions.